Mouse Panx1 Is Dispensable for Hearing Acquisition and Auditory Function - Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Mazzarda, Flavia; Nardin, Chiara; Pasquini, Miriam; Chiani, Francesco; Raspa, Marcello; Scavizzi, Ferdinando; Carrer, Andrea; Crispino, Giulia; et al. (Frontiers in Molecular Neuroscience, 2017)
Panx1 forms plasma membrane channels in brain and several other organs, including the inner ear. Biophysical properties, activation mechanisms and modulators of Panx1 channels have been characterized in detail, however the impact of Panx1 on auditory function is unclear due to conflicts in published results. To address this issue, hearing performance and cochlear function of the Panx1−/− mouse strain, the first with a reported global ablation of Panx1, were scrutinized. Male and female homozygous (Panx1−/−), hemizygous (Panx1+/−) and their wild type (WT) siblings (Panx1+/+) were used for this study. Successful ablation of Panx1 was confirmed by RT-PCR and Western immunoblotting in the cochlea and brain of Panx1−/− mice. Furthermore, a previously validated Panx1-selective antibody revealed strong immunoreactivity in WT but not in Panx1−/− cochleae. Hearing sensitivity, outer hair cell-based “cochlear amplifier” and cochlear nerve function, analyzed by auditory brainstem response (ABR) and distortion product otoacoustic emission (DPOAE) recordings, were normal in Panx1+/− and Panx1−/− mice. In addition, we determined that global deletion of Panx1 impacts neither on connexin expression, nor on gap-junction coupling in the developing organ of Corti. Finally, spontaneous intercellular Ca2+ signal (ICS) activity in organotypic cochlear cultures, which is key to postnatal development of the organ of Corti and essential for hearing acquisition, was not affected by Panx1 ablation. Therefore, our results provide strong evidence that, in mice, Panx1 is dispensable for hearing acquisition and auditory function.